Mindfulness for therapists : understanding mindfulness for professional effectiveness and personal well-being - Zarbock, Gerhard; Lynch, Siobhan, Ph. D.; Ammann, Axel; Ringer, Silka (Chichester, West Sussex : John Wiley & Sons Ltd., 2014)
Mindfulness for Therapists presents an innovative eight-week mindfulness protocol designed to aid therapists which may be worked through alone or in small groups. It presents the first complete mindfulness program designed to improve the personal and professional well-being and effectiveness of therapists themselves. The book features an 8-week introduction to mindfulness in the form of exercises designed to help therapists develop their own meditation practice and apply it to their lives Integrates key research that includes the Five Facets of Mindfulness, the Three-Person-Perspectives approach, and the neurobiological foundations of mindfulness training. The book is supported by online meditations and exercises for therapists.
Welcome -- Mindfulness -- Bringing mindfulness into your life -- Extending your practice -- Short manual for running a group based on the presented material -- Frequently asked questions (FAQ).
Description based upon print version of record.
Includes bibliographical references and index.
Keywords: Awareness; Health personnel; Meditation -- Therapeutic use; Mindfulness; Psychotherapists -- Mental health; Mindfulness (Psychology); Psychotherapists -- Mental health; Meditation -- Therapeutic use; Awareness; Mindfulness (Psychology); Awareness; Meditation -- Therapeutic use; Psychotherapists -- Mental health; Electronic books